Perlis’s Tourism: Accomodation and facilities determination based on GIS application - Zainal, Norfariza; Mokhtar, Ernieza Suhana; Abdul Wahab, Siti Maryam; Yusof, Nor Azlan; Nayan, Surina (2013)
Accommodation is one of the important aspects in the tourism development which is the competitive tourist sector. By providing adequate information of accommodation in terms of place, availability of facilities and price, it will be easier for travellers to choose any accommodation that meets their needs and budget. Thus, the aim of this project is to develop a one-stop centre of information for accommodation in Perlis to support the needs of tourists. The goals of the project are to prepare the georeferenced location, ii) detailed information about the facilities and the rate of each accommodation provided. As a result, the information on accommodation can retrieve from the centre of information, and it will help tourists in planning their vacation. In addition, the project will aid the Ministry of Tourism, Perlis office to manage and update every hotel and homestay information surrounding Perlis.